STUDI TENTANG PENGGUNAAN PAKAN KOMERSIL YANG DICAMPUR DENGAN BAKTERI Bacillus coagulans TERHADAP PERFORMA Litopenaeus vannamei - Suri, Ratna; Putri, Berta; Susanti, Oktora (University of Lampung, 2018)
In vaname shrimp cultivation, one of the problem that often arise is the high production costs in provision of feed The use of probiotics is a viable alternative to reduce production costs. The probiotic that used in this research was Bacillus coagulans bacteria. This research was aimed to know the effect of the use of Bacillus coagulans bacteria in feed on weight growth, lenght growth, survival rate, feed conversion ratio, and water quality in cultivation on vaname shrimp. Post larvae 10 vaname shrimp as much as 25 pcs were placed in each aquariums with volume 50x40x40 cmfor 30 days. The probiotics with dosage of treatment 30 ml/kg; 50 ml/kg; 70 ml/kg were combined in commercial feed with the protein content 32%. The shrimp feeding method that used in this research was blind feeding with 4 times feeding a day. The result showed that the best treatment was 70 ml/kg feed giving the significant effect on weight growth, length growth, andfeed conversion ratio. The treatments didn't effect on SR however. The water quality such as DO, temperature, salinity, and was TAN still in the optimum value.